Bayesian Inference Associates Rare KDR Variants With Specific Phenotypes in Pulmonary Arterial Hypertension. (February 2021) - Swietlik, Emilia M.; Greene, Daniel; Zhu, Na; Megy, Karyn; Cogliano, Marcella; Rajaram, Smitha; Pandya, Divya; Tilly, Tobias; Lutz, Katie A.; Welch, Carrie C.L.; Pauciulo, Michael W.; Southgate, Laura; et al.
Abstract : Background: Approximately 25% of patients with pulmonary arterial hypertension (PAH) have been found to harbor rare mutations in disease-causing genes. To identify missing heritability in PAH, we integrated deep phenotyping with whole-genome sequencing data using Bayesian statistics. Methods: We analyzed 13 037 participants enrolled in the NBR study (NIHR BioResource—Rare Diseases), of which 1148 were recruited to the PAH domain. To test for genetic associations between genes and selected phenotypes of pulmonary hypertension, we used the Bayesian rare variant association method BeviMed. Results: Heterozygous, high impact, likely loss-of-function variants in the kinase insert domain receptor ( KDR ) gene were strongly associated with significantly reduced transfer coefficient for carbon monoxide (posterior probability=0.989) and older age at diagnosis (posterior probability=0.912). We also provide evidence for familial segregation of a rare nonsense KDR variant with these phenotypes. On computed tomographic imaging of the lungs, a range of parenchymal abnormalities were observed in the 5 patients harboring these predicted deleterious variants in KDR . Four additional PAH cases with rare likely loss-of-function variants in KDR were independently identified in the US PAH Biobank cohort with similar phenotypic characteristics. Conclusions: The Bayesian inference approach allowed us to independently validate KDR, which encodes for the VEGFR2 (vascular endothelial growth factor receptor 2), as a novel PAH candidate gene. Furthermore, this approach specifically associated high impact likely loss-of-function variants in the genetically constrained gene with distinct phenotypes. These findings provide evidence for KDR being a clinically actionable PAH gene and further support the central role of the vascular endothelium in the pathobiology of PAH. Abstract : Supplemental Digital Content is available in the text.